Analysis Of Size, ROA, And Growth Of Corporate Value; With Variable Capital Structure As Intervening - Kartika Rusnindita Rusnindita (Universitas Trunojoyo Madura, 2020)
The purpose of research to test the effect of SIZE, ROA, and GROWTH on Corporate Value, with Capital Structure as intervening variables in chemical base-based companies. The research approach uses quantitative approach with analysis tool uses SEM Wrap-PLS. The results of the research are: SIZE has a negative effect on Corporate Value; ROA has a positive effect on Corporate Value; Growth has no effect on Corporate Value; Capital Structure has a positive effect on Corporate Value; SIZE does not affect the Capital Structure; ROA has a positive effect on the Capital Structure; Growth has a positive effect on the Capital Structure; Capital Structure mediate indirectly positively between SIZE towards Corporate Value; The Capital Structure mediate positively indirectly between ROA and Corporate Value; Capital Structure mediate indirectly between Growth and Corporate Value.